COMMUNICATION MANAGEMENT OF TELUK AGUNG VILLAGE FARMER GROUP IN MARKETING COFFEE CROPS: Case Study in Teluk Agung Village, Mekakau Ilir District, South OKU Regency - oktalia, Oktalia; Yusalia, Henny; Azarkasyi, Badarudin (Asosiasi Prodi Manajemen Administrasi Pendidikan Indonesia (APMAPI), 2025)
Coffee is one of Teluk Agung Village's leading commodities and has high economic potential for farmers. However, limited market access and weak communication strategies cause crop yields not to be fully optimal. This study aims to find out how the farmer group in Teluk Agung Village communicates in the marketing of coffee crops and to understand the dynamics that occur within the farmer group. This study uses a qualitative approach with a descriptive method. The informants in this study consisted of five people, including chairpersons, secretaries, and members of farmer groups in Teluk Agung Village, Mekakau Ilir District, Ogan Komering Ulu Selatan Regency. Data collection techniques are done through observation, in-depth interviews, and documentation. The theory used in this study is group achievement theory, which emphasizes members' contribution, cooperation, and the collective achievement of results. The study results show that communication in farmer groups is active and functional through discussions, division of roles, and coordination in marketing coffee. Group dynamics shown through participation, trust, and mutual awareness also strengthen the effectiveness of cooperation, thereby supporting the achievement of group goals in increasing the selling value of coffee crops.